Anonymous
Anonymous asked in Arts & HumanitiesDancing · 1 month ago

algebra 2 ?

actor the quadratic expression completely.

2x^2+7x+3=_______

Update:

please show work or explain how u got it 

7 Answers

Relevance
  • 4 weeks ago

    It's a quadratic, so try the quadratic formula:

    x = (-7 +/- sqrt(7^2 - 4*2*3))/(2*2) = (-7 +/-sqrt(49 - 24))/4 = (-7 +/- 5)/4 = -3 or -1/2so (2x+1)(x+3)or.... 2 = 2*1 and 3 = 3* 17 = 2*3 + 1*1so (2x+1)(x+3)or==> (2x^2 + x) + (6x + 3)==> x(2x+1) + 3(2x+1)==> (2x+1)(x+3)

  • 1 month ago

    2x^2 + 7x + 3

    Factors to

    ( 2x + 1)(x + 3

  • 1 month ago

    2x^2 + 7x + 3 

    Factors to 

    ( 2x + 1)(x + 3) 

  • sepia
    Lv 7
    1 month ago

    2x^2 + 7x + 3

    = 2x^2 + 6x + x + 3

    = 2x(x + 3) + (x + 3)

    = (2x + 1)(x + 3)

  • What do you think of the answers? You can sign in to give your opinion on the answer.
  • 1 month ago

    Break up the middle term into two terms, i.e. find two numbers with a sum of 7 and a product of 2*3=6. So they must be 1 and 6. So we have:

    = 2x^2 + x + 6x + 3

    Find a common factor for the first two terms, and find a common factor for the next two terms:

    = x(2x + 1) + 3(2x + 1)

    Now factor using (2x + 1) as a common factor:

    = (x + 3)(2x + 1)

    If the above doesn't work, first find the roots using the quadratic formula:

    x = (-7 +/- sqrt(7^2 - 4*2*3)) / (2*2)

    x = (-7 +/- sqrt(49 - 24)) / 4

    x = (-7 +/- sqrt(25)) / 4

    x = (-7 +/- 5) / 4

    x = (-12 or -2) / 4

    x = -3 or -0.5

    So the original expression must be some multiple of:

    (x + 3)(x + 0.5) which is the same as x^2 + 3.5x + 1.5

    We need to multiply that by 2 to get back to the original expression.

    So we have 2(x + 3)(x + 0.5), which is the same as (x + 3)(2x + 1)

  • 1 month ago

    (2x+5)(x+1)=2x²+5x+2x+5=2x²+7x+5

    So 2x²+7x+3=-2

  • alex
    Lv 7
    1 month ago

    2x^2+7x+3=(2x+1)(x+3)

Still have questions? Get answers by asking now.